MANAJEMEN SUMBER DAYA MANUSIA TERHADAP PRODUKTIFTAS USAHA MELALUI KUALITAS SDM DI INDUSTRI KECIL DAN MENENGAH (IKM) DI PROVINSI SUMATERA UTARA - Sunday Ade Sitorus; Winda Ardiani; Hanna Damanik; Anto Tulim; Lasma Siagian; SUNDAY ADE SITORUS (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to determine whether planning for HR procurement, organizing HR and providing motivation has a direct or indirect effect on the productivity of Small and Medium Industries (IKM) through the quality of human resources. This study focuses on human resource management activities such as HR procurement planning, HR organization and motivation which only affects other variables, namely the productivity of Small and Medium Industries (IKM) through the intervening variable of HR quality. In this study, the independent variable is HR procurement planning, HR organization and motivation, the dependent variable is Small and Medium Industry (IKM) productivity, while the intervening variable is HR quality, where data analysis uses PLS 3.0 path analysis. This research is a quantitative descriptive research method using path analysis, with a sample of 100 people, using probability sampling. Partially, only the motivational variable for HR has a positive and significant effect on the variable quality of HR in Small and Medium Industries (IKM) and the work productivity variable for Small and Medium Industries (IKM) in North Sumatra. Meanwhile, simultaneously, the variables of HR procurement planning, HR organizing and motivating HR have a positive and significant effect on the work productivity of Small and Medium Industries (IKM) in North Sumatra through the variable of HR quality in Small and Medium Industries (IKM). Through the results of the study, only the motivational variable for HR has indirect implications for the work productivity of Small and Medium Industries (IKM) in Indonesia through the quality of HR in Small and Medium Industries (IKM), where by providing more motivation to businesses, Small and Medium Industries and Medium Enterprises (IKM) will be able to improve the quality of their human resources while at the same time increasing the work productivity of Small and Medium Industries (IKM).